2019
DOI: 10.2147/cmar.s200566
|View full text |Cite|
|
Sign up to set email alerts
|

<p>MicroRNA-665 inhibits the oncogenicity of retinoblastoma by directly targeting high-mobility group box 1 and inactivating the Wnt/&beta;-catenin pathway</p>

Abstract: Purpose: Previous studies have revealed that microRNA-665 (miR-665) is dysregulated in a variety of human cancers. However, little is known regarding its expression profiles and functions in retinoblastoma (RB). Therefore, the aims of our study were to evaluate miR-665 expression in RB and determine the precise roles of miR-665 in the progression of RB. Patients and methods: Herein, RT-qPCR was used to determine miR-665 expression levels in RB tissues and cell lines, and a series of functional experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
(50 reference statements)
2
21
0
Order By: Relevance
“…In the field of RB research, a variety of different miRNAs have been revealed to be aberrantly expressed, and their anomalous expression plays important roles in the regulation of multiple cancer-related processes, including cell survival, proliferation, apoptosis, metastasis, angiogenesis and epithelial-mesenchymal transition (10). For instance, miR-98 (11), miR-186 (12) and miR-665 (13) are weakly expressed in RB and restrain tumor progression; on the contrary, miR-93 (14), miR-106b (15) and miR-198 are overexpressed in RB and promote tumor aggressiveness. miR-936 has been reported to exert important effects on the progression of non-small cell lung cancer (16) and glioma (17).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of RB research, a variety of different miRNAs have been revealed to be aberrantly expressed, and their anomalous expression plays important roles in the regulation of multiple cancer-related processes, including cell survival, proliferation, apoptosis, metastasis, angiogenesis and epithelial-mesenchymal transition (10). For instance, miR-98 (11), miR-186 (12) and miR-665 (13) are weakly expressed in RB and restrain tumor progression; on the contrary, miR-93 (14), miR-106b (15) and miR-198 are overexpressed in RB and promote tumor aggressiveness. miR-936 has been reported to exert important effects on the progression of non-small cell lung cancer (16) and glioma (17).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has revealed that miR-665 can regulate EMT-related proteins by targeting mRNAs in various cancers. 16,17 It has also been reported that miR-665 is down-regulated in osteosarcoma, 18 retinoblastoma, 19 and ovarian cancer, 20 but is up-regulated in non-small cell lung cancer 21 and breast cancer. 22 However, the functional role of miR-665 in GC remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Accumulated evidence has confirmed the crucial regulatory role of miRNAs in diverse physiological and pathological processes, including cell proliferation, cell death, differentiation, metabolism, and even carcinogenesis [12][13][14]. A number of miRNAs are aberrantly expressed during the genesis and progression of RB [15][16][17]. Thus, it is urgently necessary to examine the specific functions of miRNAs in RB and to delineate their mechanism of action.…”
Section: Introductionmentioning
confidence: 99%